2021
DOI: 10.17159/2310-3833/2021/vol51n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles in Physiotherapy and Occupational Therapy students: an exploratory study

Abstract: BACKGROUND: Learning styles of health care professionals are unique and tend to be profession- specific. This study aimed to compare the learning styles of undergraduate occupational therapy and physiotherapy students and to determine the relationship between preferred learning styles, demographic factors, and academic performance METHOD: The study design was a cross-sectional, descriptive study. Undergraduate occupational therapy and physiotherapy students completed a self-developed questionnaire and the Gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The findings of a study by Deborah et al (2018) showed that students preferred kinesthetic learning the most. The same finding was also found by Olivier et al (2021) that the predominant preferred learning styles are the collaborative and participatory styles. This learning style is consistent with the kinesthetic style as well as with Mehmood's (2020) finding that students show a tendency to actively experiment (AE) in their learning, indicating that they want to be actively involved in their own learning process rather than just listening to lectures delivered in the traditional method.…”
Section: Statement Of Problemsupporting
confidence: 80%
See 3 more Smart Citations
“…The findings of a study by Deborah et al (2018) showed that students preferred kinesthetic learning the most. The same finding was also found by Olivier et al (2021) that the predominant preferred learning styles are the collaborative and participatory styles. This learning style is consistent with the kinesthetic style as well as with Mehmood's (2020) finding that students show a tendency to actively experiment (AE) in their learning, indicating that they want to be actively involved in their own learning process rather than just listening to lectures delivered in the traditional method.…”
Section: Statement Of Problemsupporting
confidence: 80%
“…One of them is to create and maintain the best way to impart knowledge to students. Identifying the preferred learning styles among students can be very arduous as there is no single style that can be said to be the best way to impart knowledge to students (Derkach & Kharitonenko, 2018;Ibrahim & Hussein, 2015;Noor Nasyikin et al, 2019;Fahim et al, 2021;Sam, 2022;Sherly Deborah et al, 2018;Olivier et al, 2021;Mehmood, 2020;Nasir et al, 2021;Quinn et al, 2018).…”
Section: Statement Of Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…And yet none of the models that we were being introduced to would fit with our wh anau. Learners have diverse learning styles and research by Olivier et al (2021) has identified that occupational therapy students prefer collaborative and participatory approaches. O'Toole (2014), in a review of teaching practices in Aotearoa, Canada, United States and Australia, found the expert-novice model widely in use within the Western tertiary education sector had limited alignment with Indigenous learning preferences.…”
Section: Cultural Dissonancementioning
confidence: 99%